Analisis Fisik Madu Akasia Setelah diproses dengan Mesin Evaporator Vacuum Cooling Four in One Skala Industri - M. Amin Muzaki; Anang Lastriyanto; Moch. Bagus Hermanto; Sandra Malin Sutan; Ary Mustofa Ahmad; Sasongko Aji Wibowo; Vincentia Veni Vera; Khoiril Anam (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2025)
Honey has significant health benefits due to its rich content of nutrients, enzymes, and bioactive compounds. However, conventional processing methods such as pasteurization can potentially degrade the physical and chemical quality of honey, including moisture content, density, total soluble solids, viscosity, and color stability. This study examines the effectiveness of the Evaporator Vacuum Cooling Four in One technology in maintaining the quality of Acacia honey compared to various pasteurization durations. The results show that vacuum cooling technology significantly preserves honey quality in terms of moisture content, density, and total soluble solids at a better level than conventional methods. Additionally, vacuum cooling optimally maintains honey's viscosity and color, demonstrating its superiority in reducing damage to bioactive components. This study is expected to contribute to the development of more efficient honey processing technology in the industry, aiming to provide high-quality honey that meets consumer health standards.